2014
DOI: 10.1080/09658211.2013.877487
|View full text |Cite
|
Sign up to set email alerts
|

Why does saccade execution increase episodic memory retrieval? A test of the top-down attentional control hypothesis

Abstract: Making repetitive saccadic eye movements has been found to increase subsequent episodic memory retrieval and also to increase subsequent top-down attentional control. We theorise that these effects are related such that saccade-induced changes in attentional processing facilitate memory retrieval. We tested this idea by examining the effect of saccade execution on retrieval conditions that differed in relative ease of consciously accessing episodic memories. Based on recent theories of episodic retrieval, we r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 74 publications
(131 reference statements)
3
22
0
Order By: Relevance
“…Lyle and Edlin performed this experimental manipulation because it has been shown in the literature that top-down attentional processes play a key role in memory tests, especially when performance is low and cognitive effort is high [34]. Results aligned with their predictions: The SIRE benefit was found when memory tasks were harder and therefore required greater top-down attentional control [28]. Crucially, they also found a memory performance benefit following vertical eye movements (for the second time), which is predicted only by their top-down attentional control account.…”
Section: Top-down Attentional Controlmentioning
confidence: 64%
See 3 more Smart Citations
“…Lyle and Edlin performed this experimental manipulation because it has been shown in the literature that top-down attentional processes play a key role in memory tests, especially when performance is low and cognitive effort is high [34]. Results aligned with their predictions: The SIRE benefit was found when memory tasks were harder and therefore required greater top-down attentional control [28]. Crucially, they also found a memory performance benefit following vertical eye movements (for the second time), which is predicted only by their top-down attentional control account.…”
Section: Top-down Attentional Controlmentioning
confidence: 64%
“…It has been shown that unilateral saccades activate the contralateral hemisphere [27]. In the context of SIRE, this would suggest that vertical eye movements should not produce a SIRE effect because they do not produce the same bilateral activation in frontal eye fields as is produced by horizontal eye movements [22,28]. In summary, the interhemispheric interaction hypothesis predicts that only horizontal eye movements should result in a performance benefit due to the inherent alternating activation of hemispheres.…”
Section: Interhemispheric Interactionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other influential accounts, primarily for EMDR, such as the working memory account (Andrade et al, 1997) or the orienting response account (Armstrong and Vaughan, 1996; Stickgold, 2002), as well as the newer top-down attentional control account from the SIRE domain (Edlin and Lyle, 2013; Lyle and Edlin, 2015) were completely ignored. Elsewhere (Phaf, submitted), I have identified crucial hidden variables based on the linking of theoretical accounts for SIRE and EMDR that may well explain the contrast between the original SIRE findings and the non-replication.…”
Section: Eye Movements Memory and Emotionmentioning
confidence: 99%